2004
DOI: 10.1063/1.1830680
|View full text |Cite
|
Sign up to set email alerts
|

Al – Si multilayers: A synthetic material with large thermoelectric anisotropy

Abstract: A synthetic material with large thermoelectric anisotropy has been prepared from a metal–semiconductor multilayer structure. By an alloying process, a multilayer stack A–B–A…, where A and B are pure aluminum and n-silicon, is produced with a thermoelectric anisotropy ΔS=S‖−S⊥≅1.5mV∕K, where S‖ and S⊥ are the absolute Seebeck coefficients along and perpendicular to the layers, respectively. The use of this synthetic material for light sensing applications is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…84 A large thermoelectric anisotropy (related to the difference of the parallel and the perpendicular values of the S) of ∼ 1.5 mV/K, was also noted 85 through the use of an Al/Si layered system. It is remarkable that such a large effect was reported in this composite, at room temperature, given that the S values are of the order of 1-10 µV/K for metals, and around 100 µV/K for semiconductors, and may indicate problems with measurement and/or interpretation.…”
Section: B Experimental Investigationsmentioning
confidence: 99%
“…84 A large thermoelectric anisotropy (related to the difference of the parallel and the perpendicular values of the S) of ∼ 1.5 mV/K, was also noted 85 through the use of an Al/Si layered system. It is remarkable that such a large effect was reported in this composite, at room temperature, given that the S values are of the order of 1-10 µV/K for metals, and around 100 µV/K for semiconductors, and may indicate problems with measurement and/or interpretation.…”
Section: B Experimental Investigationsmentioning
confidence: 99%
“…This framework first utilized the Kirchhoff Circuit Laws (KCL) to calculate the equivalent properties in the directions parallel and perpendicular to the layer plane, and then employed a tensor transformation to obtain the properties in an arbitrary direction. The validity of this simplified mathematical model has been demonstrated by multiple studies using either finite element simulations [16,17] or experimental simplified mathematical model has been demonstrated by multiple studies using either finite element simulations [16,17] or experimental measurements [12,[18][19][20][21][22][23][24][25][26][27]. In addition to the lamella configuration, composite materials with aligned one-dimensional (1-D) inclusions, as suggested by Goldsmid [1,4], are also good candidates for transverse TE.…”
Section: Introductionmentioning
confidence: 96%
“…Nanotechnology is a major example345678. Another example is the transverse TE effect, or the off-diagonal TE effect, which essentially develops in tilted layered materials9101112131415161718. The previous studies have revealed various unusual phenomena arising from this effect including the gigantic voltage generation in incline-oriented nanometer-scale thin films91011, and enhanced power factors in artificial tilted multilayer materials17.…”
mentioning
confidence: 99%
“…Transverse TE devices exhibit distinct functions as compared to the ordinary TE devices as follows; (i) the voltage signal develops perpendicular to the applied ΔT (see the schematic in Fig. 1a)9101112131415161718, (ii) compatibility between n-type and p-type TE material19 is not necessary since either of them is sufficient to construct the device (the polarity of the TE voltage can be reversed by reversing the tilt-direction of the layers), and (iii) the macroscopic physical properties of the multilayer material can be tuned widely by changing the combination and the periodicity of the constituents12131415161718. These features provide us new degree of freedom in designing alternative TE devices.…”
mentioning
confidence: 99%